Effectiveness of Acceptance and Commitment Therapy on Anxiety, Cognitive Avoidance, and Empathy of Couples Visiting Counseling Centers in Ahvaz City, Iran - Shabnam Mohammadian; Parviz Asgari; Behnam Makvandi; Farah Naderi (Gonabad University of Medical Sciences, 2021)
Background: Anxiety can reduce the couples' self-confidence and damage their mental health. The present study aimed to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on anxiety, cognitive avoidance, and empathy among couples visiting counseling centers in Ahvaz City, Iran, in 2020. Methods: The research method was quasi-experimental with a pre-test, post-test design, follow-up, and a control group. The statistical population consisted of all couples with low marital adjustment who were referred to the psychological centers of Ahvaz in 2019. Using a convenience sampling method, 30 participants were selected and randomly divided into experimental and control groups (n=15 per group). The research instruments included the symptom checklist-90-revised, the cognitive avoidance questionnaire, and the basic empathy scale. The experimental group underwent eight 90-min sessions (one session per week) of ACT, and the control group did not receive any intervention. The follow-up was performed after 45 days. Repeated-measures ANOVA was used to analyze the data in SPSS. Results: ACT effectively decreased anxiety and cognitive avoidance and increased empathy among couples in the experimental group (P<0.001). The Mean±SD pre-test and post-test scores of anxiety in the experimental group were 23.33±2.89 and 18.93±3.36, respectively, which decreased compared to the post-test mean score (24.27±2.96) of the control group. Conclusion: ACT decreased anxiety and cognitive avoidance and significantly increased empathy in married individuals. ACT can improve empathy in couples involved in marital conflicts.